2004
DOI: 10.1159/000078176
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Consequences of a Deep Breath Revisited

Abstract: About two decades ago, a model was proposed for surfactant release by lung distension. This model implies rapid fusion of lamellar bodies (LBs) with the plasma membrane followed by quick release of surfactant into the alveolus, as reflected by immediate facilitation of lung inflation after a single deep breath. Recent experimental evidence indicates that this two-pool model (intracellular versus alveolar surfactant pool) has to be refined by introducing a third pool, which resides in fused but non-released LBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…1D). In vivo, a mechanical strain of the lung epithelium (occurring as a result of a deep breath, such as a yawn or a sigh or during exercise) is believed to be the major stimulus for surfactant secretion (31)(32)(33)(34); however, ATP is also present in the pulmonary hypophase, the thin liquid layer lining the alveolar epithelium (35). In particular, it is believed that mechanical strain, along with inducing a rise in [Ca 2+ ] c , leads to ATP release from ATII cells (36).…”
Section: Resultsmentioning
confidence: 99%
“…1D). In vivo, a mechanical strain of the lung epithelium (occurring as a result of a deep breath, such as a yawn or a sigh or during exercise) is believed to be the major stimulus for surfactant secretion (31)(32)(33)(34); however, ATP is also present in the pulmonary hypophase, the thin liquid layer lining the alveolar epithelium (35). In particular, it is believed that mechanical strain, along with inducing a rise in [Ca 2+ ] c , leads to ATP release from ATII cells (36).…”
Section: Resultsmentioning
confidence: 99%
“…Surfactant release after a deep inspiration could also affect airway impedance, especially that of the small airways [301]. It is crucial to establish the relative importance of the various contributing factors involved in stretch-induced smooth muscle response and their relevance to asthma.…”
Section: Stretch-induced Release Of Transmitters In the Parenchyma Anmentioning
confidence: 99%
“…18,66,69,72). In particular, tissue stretch (ϭ tensile strain) has already been shown to be an important determinant of surfactant secretion in alveolar type II (AT II) cells (2,15,36,47,71,73). Studies on single cells revealed that stretch induces an elevation of the intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) (23, 73), perhaps via mechanosensitive ion channels like the wellcharacterized transient receptor potential (TRP) vanilloids (reviewed in Refs.…”
mentioning
confidence: 99%